Semantic enterprise application integration for business processes : service-oriented frameworks - Mentzas, Gregoris, 1960-; Friesen, Andreas. (Business Science Reference, 2010)
"This book provides methods that allow for access to corporate and customer data independent of where it resides"--Provided by publisher.